Program Pengabdian Masyarakat Peningkatan Kapasitas dan Kualitas Produk Kue Tradisional Randupangan: Community Service Program for the Improvement of Capacity and Quality of Traditional Cake Product in Randupadangan - Ampar Jaya Suwondo; Navik Kholili; Agung Bayu Murti (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Community service carried out in Randupadangan Village, Menganti District, Gresik Regency stems from issues of low production capacity, poor product quality, and conventional marketing strategies in traditional cake businesses. Partner businesses, managed by local micro-entrepreneurs, face challenges due to limited production equipment, poor hygiene practices, and limited digital market penetration, requiring a structured intervention. This program is designed with a Participatory Learning and Action approach that actively involves partners in every stage of the activity, from problem identification to solution design to evaluation. Interventions are made through the procurement and use of Appropriate Technology, such as semi-automatic drying ovens and large-capacity deep fryers; training in hygienic production techniques; packaging improvements; and digital marketing training with social media and marketplace integration. The results of the activities show a 30% increase in production capacity, a 30% increase in business assets, and a 60% increase in partner skills in operating tools, production strategies, and digital marketing, accompanied by a 20% increase in online sales. These achievements not only improve process efficiency and product quality but also strengthen the competitiveness of partner businesses by enhancing brand identity and expanding market access. This program demonstrates that integrating appropriate technology and participatory digital strategies can serve as a sustainable empowerment model for traditional culinary MSMEs, though the limitations of mentoring time and the scope of product diversification remain challenges to be addressed in future community service.